2020
DOI: 10.1007/s11440-020-01076-7
|View full text |Cite
|
Sign up to set email alerts
|

A state-dependent hypoplastic model for methane hydrate-bearing sands

Abstract: The mechanical behaviors of methane hydrate-bearing sands (MHBS) are largely affected by the presence of methane hydrate, temperature, and pore pressure. In this study, we present a simple hypoplastic model for MHBS. Methane hydrate saturation is included as a state parameter affecting the mechanical behaviors of MHBS. A new phase parameter is introduced to account for the coupled effects of temperature and pore pressure on the mechanical behaviors of MHBS. The phase parameter can be determined by a simple fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Ng et al adopted the phase parameter L in their constitutive model, but the phase parameter L was only determined by the iterative method . Liu et al suggested a piecewise function for the new phase parameter L ′ at two different temperature–pore pressure areas . However, the method for dividing the area was still troublesome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ng et al adopted the phase parameter L in their constitutive model, but the phase parameter L was only determined by the iterative method . Liu et al suggested a piecewise function for the new phase parameter L ′ at two different temperature–pore pressure areas . However, the method for dividing the area was still troublesome.…”
Section: Discussionmentioning
confidence: 99%
“…42 Liu et al suggested a piecewise function for the new phase parameter L′ at two different temperature−pore pressure areas. 43 However, the method for dividing the area was still troublesome. This study adopts the phase state parameter θ to characterize the temperature and pore pressure condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This basic model has several merits such as simplicity and robustness in numerical simulation. These advantages make it an interesting stand-alone model for many applications [30,31,36,38,46] and further developments [19,20,39].…”
Section: A Basic Hypoplastic Modelmentioning
confidence: 99%